2022
DOI: 10.15700/saje.v42n1a2025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teachers’ demographic factors towards workplace spirituality at secondary school level

Abstract: Workplace spirituality is recognised as the inner state of individuals and an aspect of their working life. In the study reported on here we aimed to unearth the effects of teachers’ demographic factors (gender, age, nature of job, academic qualification, marital status, designation, teaching experience, and district) towards workplace spirituality in secondary schools. This study was a descriptive research and a cross-sectional survey research design was applied. The participants were 3,050 secondary school t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…Moreover, it was revealed that the designation had a significant effect on job stress. The results are in congruence with the study of Aslam et al (2022), who concluded that designation is a significant demographic factor for workplace spirituality. It is perhaps due to the reason that PSTs are the lowest category teachers who have a small grade, less salaries and less physical as well as human resources but are answerable before a number of authorities, i.e., Assistant Education Officer, Deputy District Education Officer, District Education Officer, Chief Executive Officer, and Monitoring Evaluation Assistants.…”
Section: Qualificationsupporting
confidence: 90%
“…Moreover, it was revealed that the designation had a significant effect on job stress. The results are in congruence with the study of Aslam et al (2022), who concluded that designation is a significant demographic factor for workplace spirituality. It is perhaps due to the reason that PSTs are the lowest category teachers who have a small grade, less salaries and less physical as well as human resources but are answerable before a number of authorities, i.e., Assistant Education Officer, Deputy District Education Officer, District Education Officer, Chief Executive Officer, and Monitoring Evaluation Assistants.…”
Section: Qualificationsupporting
confidence: 90%
“…Workplace spirituality inculcates beyond practices of inter-connectivity and a feeling of believe among individuals, who're a part of a particular work system, which finally instigate cooperative feelings and result in an usual organizational lifestyle this is pushed through motivation, exemplified by means of a fine response, and unanimity and harmony a number of the individuals, consequently uplifting the cumulative overall performance of the individuals, and in flip assisting to the organizational excellence as an entire (Afsar & Rehman, 2015;Aslam, Mazhar, Sarwar & Chaudhary 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Rev. EntreLinguas,Araraquara, v. 9, n. 00, e023013, 2023. e-ISSN: 2447-3529 DOI: https://doi.org/10.29051/el.v9i00.18030 17Características como ética, crença em uma força superior, integridade, confiança, gentileza, respeito, senso de comunidade e paz nas organizações, funcionários inspirados, humanizados e cheios de compaixão, criam um paradigma que é chamado espiritualidade no local de trabalho(AĞALDAY, 2022;ASLAM et al, 2022). Dessa forma, importância é possível notar a relevância de se trabalhar a espiritualidade no ambiente escolar, que é onde o indivíduo permanece por longos anos antes de ingressar no mercado de trabalho.…”
unclassified